Evolution of pharmacist roles in antimicrobial stewardship: A 20-year systematic review - Vrinda Nampoothiri; Mohamed Hisham; Oluchi Mbamalu; Zubair Umer Mohamed; Sanjeev K. Singh; Esmita Charani (International Journal of Infectious Diseases)
Introduction: Whilst pharmacists are recognized as key contributors to antimicrobial stewardship (AMS) programs, the extent of their participation varies in different countries. We report a systematic review of pharmacist roles in AMS over 20 years. Methods: A systematic review of the literature describing pharmacist-led or driven AMS and its outcomes published in English between January 01, 2000, and June 30, 2020, was conducted across the main databases for research publication. Results: The analysis included 111 papers, of which 77.5% (86/111) were from high-income countries (HIC) predominantly from the USA. While pharmacist-led or driven AMS interventions were reported only from HICs in the early 2000s, the review found a progressive rise in such studies from all income settings with audit and feedback being the most frequent intervention reported. Between 2016 and 2020, studies on pharmacists-led or driven outpatient AMS and interventions related to beta-lactam or penicillin allergy were reported from HICs. Key outcomes reported include improved appropriateness of antimicrobial therapy and decreased consumption of antimicrobials. Conclusion: Existing evidence demonstrates the positive impact of pharmacists’ involvement in AMS. There needs to be a concerted effort in facilitating pharmacist roles in AMS across all countries, irrespective of income setting.